Stability analysis with respect to two measures of impulsive systems under structural perturbations - Martynyuk, A. A.; Stavroulakis, I. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
The asymptotic stability with respect to two measures of impulsive systems under structural perturbations is investigated. Conditions of asymptotic (ρ0, ρ)-stability of the system in terms of the fixed signs of some special matrices are established.